Pengaruh Kombinasi Antipsikotik Tehadap Efek Samping Sindrom Ekstrapiramidal Pasien Skizofrenia Rawat Inap Rumah Sakit Jiwa Sambang Lihum Banjarbaru - Helmina wati; Rahmi Hidayati; Muhammad Rizky Wardani (Borneo Journal of Pharmascientech, 2024)
The most effective therapeutic management in schizophrenia patients is antipsychotic therapy. Antipsychotic groups are divided into two categories: first-generation and second-generation antipsychotics. Antipsychotic administration can cause side effects such as extrapyramidal symptoms. This study aims to determine the effect of giving a combination of antipsychotics on the side effects of extrapyramidal syndrome in hospitalized schizophrenia patients at Sambang Lihum Mental Hospital. This study employed a non-experimental observational analytic approach with prospective data collection. The study population consisted of all schizophrenia patients who were hospitalized between January and February 2022. The sample size was 122 patient medical records, obtained through purposive sampling. The instruments used to measure the variables included respondent characteristics (age, gender, latest education, occupation, marital status, history of diagnosis, and history of extrapyramidal syndrome) and the incidence of extrapyramidal syndrome side effects, which were documented in essays written by the researcher. The data analysis employed univariate (frequency, percentage) and bivariate (chi-square test) techniques. The results of the study yielded a description of the administration of antipsychotic combinations in hospitalized schizophrenia patients at Sambang Lihum Mental Hospital. The most prevalent combination was the Atypical-Typical combination, which was administered to 58.2% of patients. There were no instances of extrapyramidal syndrome side effects from the administration of a combination of antipsychotics, with 86.9% of patients experiencing no adverse effects. The administration of a combination of antipsychotics does not appear to affect the incidence of extrapyramidal syndrome in schizophrenic patients.